Estudo citogenético de seis espécies da família Loricariidae (Siluriformes) pertencentes às bacias dos rios Paranaíba e Tocantins - Correia, Vanessa Carolina de Sena (2010)
CHAPTER II: The Hypostominae subfamily comprises 45 genera, and in only five (Hypostomus, Liposarcus, Rhinielepis, Pogonopoma and Pterygoplichthys) some sort of cytogenetic work has been developed, being Hypostomus genus the largest in number of karyotyped species. Four species of the genus Hypostomus from Araguari and Tijuco rivers, Uberlândia-MG, were analyzed: H. regani, H. paulinus, H. margaritifer e H. strigaticeps, through cytogenetic techniques such as conventional staining, silver nitrate impregnation, C-banding and fluorochromes CMA3 and Hoechst 33258. In the conventional analysis H. regani presented 2n = 72, 10m+18sm+44st/a; H.strigaticeps 2n = 74, 6m+14sm+54st/a; H. margaritifer 2n = 74, 10m+24sm+40st/a, with an individual presenting an unusual heteromorphic metacentric pair on the size, and H. paulinus 2n=76, 6m+12sm+58st/a. The impregnation with silver nitrate showed multiple NORs, for the most species examined, except H. paulinus. The heterochromatin is distributed in the interstitial and telomeric regions. Staining with CMA3 showed positive markings for H. paulinus, H. margaritifer and H. strigaticeps, and negative bands in H. regani, H. margaritifer. Hoechst staining showed positive fluorescent bands in H. regani, H. strigaticeps. The results obtained in this study contribute to a better characterization of Hypostomus cytogenetics and understanding of evolution within the group and the Loricariidae family. H. regani and H. margaritifer. Hoechst staining showed fluorescent bands in H. regani and H. strigaticeps. The results obtained in this study contribute to a better cytogenetics characterization of Hypostomus and understanding of evolution within the group and the Loricariidae family. CHAPTER III: It is estimated that approximately 70 species of the Loricariidae family have been studied cytogenetically. This study aimed to characterize the karyotype of Squaliforma emarginata, which is cited by Artoni et al. (2001) as Hypostomus emarginatus and Pterygoplichthys joselimaianus. Specimens were collected in Porto Nacional -TO, the reservoir formed by damming the waters of the Tocantins River, for the implementation of the Power Plant Luis Eduardo Magalhaes. We performed cytogenetic studies by conventional staining, silver nitrate impregnation, C-banding, fluorochromes, CMA3 and Hoechst. The conventional analysis of S. emarginata showed 2n=52, 14m+2sm+36st and P. joselimaianus 2n=52, 20m+22sm+10st. Impregnation with silver nitrate in S. emarginata showed variation in the pattern of NORs between individuals, while P.joselimaianus showed single NORs. The heterochromatin is distributed in the interstitial and telomeric regions. Staining with CMA3 showed positive markings in S. emarginata corresponding to heterochromatin associate the AgRONs, while the dye Hoechst showed negative bands in both species. In P. joselimaianus staining CMA3 + showed heterochromatin rich in GC, confirmed whit Hoechst negative staining. The results obtained in this study are intended to understand the mechanism of evolution, to explain the taxonomic determinations and contribute to future conservation studies for these species.